Aerobic endurance training improves soccer performance - Helgerud, J.; Engen, L. C.; Wisloff, U.; Hoff, J. (Medicine & Science in Sports & Exercise, 2001)
Purpose: The aim of the present study was to study the effects of aerobic training on performance during soccer match and soccer specific tests. Methods: Nineteen male elite junior soccer players, age 18.1 +/- 0.8 yr, randomly assigned to the training group (N = 9) and the control group (N = 10) participated in the study. The specific aerobic training consisted of interval training, four times 4 min at 90-95% of maximal heart rate, with a 3-min jog in between, twice per week for 8 wk. Players were monitored by video during two matches, one before and one after training. Results: In the training group: a) maximal oxygen uptake (VO2max) increased from 58.1 +/- 4.5 mL.kg-1.min-1 to 64.3 +/- 3.9 mL.kg-1.min-1 (P < 0.01); b) lactate threshold improved from 47.8 +/- 5.3 mL.kg-1.min-1 to 55.4 +/- 4.1 mL.kg-1.min-1 (P < 0.01); c) running economy was also improved by 6.7% (P < 0.05); d) distance covered during a match increased by 20% in the training group (P < 0.01); e) number of sprints increased by 100% (P < 0.01); f) number of involvements with the ball increased by 24% (P < 0.05); g) the average work intensity during a soccer match, measured as percent of maximal heart rate, was enhanced from 82.7 +/- 3.4% to 85.6 +/- 3.1% (P < 0.05); and h) no changes were found in maximal vertical jumping height, strength, speed, kicking velocity, kicking precision, or quality of passes after the training period. The control group showed no changes in any of the tested parameters. Conclusion: Enhanced aerobic endurance in soccer players improved soccer performance by increasing the distance covered, enhancing work intensity, and increasing the number of sprints and involvements with the ball during a match.